Emprego de técnica dedicada de análise de imagem na avaliação do produto GT no desempenho da floculação - Moreno, Pamela [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Flocculation is a paramount step in water treatment for public supply, in addition, is essential to remove the particulate material. The knowledge about the distribution of the flocculent particles size becomes important to the flocculent particles size becomes important to understand the process of flocs removal and the treatment technology that must be adopted. In this study was evaluated the product of the average velocity gradient flocculation (Gf) by time of flocculation (Tf), GT is also defined as Camp number (NC), according to the particle size distribution (PSD). In this case, the technique of image treatment was used to obtain the PSD and the others representatives parameters. Wete investigated different values of NC (18000, 24000, 36000, 54000 e 72000) for evaluation of the sedimentation efficiency in different associated velocities (0,5;, 1,5; 2,5; 3,5 e 5.0 cm/min). The results show that NC is fundamental for the sedimentation performance in all velocities. For the same NC the average of the velocity gradient was determinant, being one of the best results for Gf= 20 s. If the velocity of sedimentation is constant (2,5 cm/min) is possible to conclude that the turbidity removal efficiency maintain 70% fir Cam numbers around 24000, 36000 and 54000. In the order hand, for extrem values 18 and 72 thousand exist a reduction of efficiency. In relation with PSD, is possible to analyze your characteristic parameter β that is sensible according with the provided energy. In conclusion, the case of study show that the increase of provided energy during flocculation results in reduction of dynamic alteration about particle size distribution, establishing inverse proportion between energy and variation of the chaacteristic parameter β. This happens due to flocs action of rupture that contributes to reach the equilibrium state of the flocculent particles in less time of flocculation. Moreover,high values of Gf and NC imply high values...

A floculação é etapa fundamental no tratamento de água para abastecimento público sendo essencial para remoção do seu papel material particulado. O conhecimento da distribuição do tamanho das partículas floculentas torna-se de grande valia para a compreensão dos processos que envolvem a remoção desses flocos bem como a tecnologia de tratamento a ser adotada. Neste trabalho, foi avaliado o produto do gradiente médio de velocidade de flobulação (Gf) pelo tempo de floculação (Tf), GT também definido como número de Camp (NC), sob a ótica da distribuição de tamanho de partícula (DTP). Para tal, foi empregada técnica dedicada de captura e de tratamento de imagens visando obtenção da DTP e de seus parâmetros representativos. Foram investigados diferentes valores de NC (18000, 36000, 54000 e 72000) para a avaliação da eficiência da sedimentação em diferentes velocidades associadas (0,5; 1,5; 2,5; 3,5 e 5,0 cm/min). Os resultados demonstraram que o desempenho da sedimentação nas distintas velocidades investigadas é sensível ao valor de NC. Para um mesmo NC o gradiente médio de velocidade foi determinante, sendo os melhores resultados obtidos para Gf de 20s. Mantida a mesma velocidade de sedimentação de 2,5 cm/min verificou-se eficiência de remoção de turbidez praticamente constante, por volta de 70% para valores de número de Camp de 24000, 36000 e 54000 ao passo que para os extremos, 18 e 72 mil houve queda na eficiência. Em relação à DTP verificou-se, por meio da análise de seu parâmetro característico β, que este é sensível a variação do produto GT, sendo mais sensível aos valores de G para determinados valores de T. Em linhas gerais, o trabalho mostrou que o aumento da energia fornecida durante a floculação implica em menor alteração da dinâmica da distribuição de tamanho de partículas, estabelecendo uma relação inversa de proporção entre energia e a variação do parâmetro...
Keywords: Floculação; Análise de imagem; Particulas; Águas residuais - Purificação; Flocculation